SDG7 - Ensure Access to Affordable, Reliable, Sustainable and Modern Energy - Nhamo, Godwell, author 646724; Nhemachena, Charles, author 646725; Nhamo, Senia, author 646726; Mjimba, Vuyo, author 646727; Savić, Ivana, author 646728; Emerald Publishing Limited (Online service) issuing body 646680 (Bingley, UK : Emerald Publishing Limited, 2019)
Defining inequality as the social, economic and political challenges of our time, this book will examine SDG10 to look ahead at how policy action might engage multiple stakeholders, involve diverse sectors and address gaps between policy and implementation to tackle key inequalities within and among countries.